PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) PEMBERDAYAAN MASYARAKAT (BST KLM DAN SKK 60 MIL) TERHADAP KESELAMATAN BERLAYAR PADA PELAYARAN RAKYAT UNTUK PARA PELAUT KAPAL LAYAR MOTOR DI PAOTERE - Joko Purnomo; Bustamin Bustamin; Ismail Ismail (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This study aims to determine the Community Empowerment Training (BST KLM and SKK 60 Mil) on Motor Sailboat Sailors at Paotere Port in Makassar City, knowing the safety of sailing on people's voyages for motor sailboat sailors in Paotere, and to determine the effect of community empowerment training (BST KLM and SKK 60 Mil) on sailing safety on people's voyages for motor sailboat sailors in Paotere. The research method used is descriptive statistical research with a quantitative approach. The research was conducted at the Paotere Fishing Port (PP), for 3 months, from April to June 2022. The results found that community empowerment training (BST KLM and SKK 60 Mil) conducted at Paotere port, such as: how to survive at sea, how to use rescue equipment, how to put out a fire, signal an emergency and so on is good it is evident from the respondents' answers, about the value of the training variable of 3,375 or (92%) including in the good category with a range of scores (900 - 3,600). The value of 3,375 is included in the good assessment interval and is close to very good. Respondents' assessment of the sailing safety variable was good, as evidenced by the 12 statement items given. The value of the sailing safety variable in Paotere of 4,500 is included in the good category with a score range of (1,200 - 4,800). The value of 4,500 is included in the good assessment interval and is close to very good, The effect of training (X) on sailing safety (Y) at Paotere port is strong with Pearson correlation value of 0.680. This means that the correlation value is in the interval 0.60 - 0.799. Or the regression test results can be seen that the t value is 9,193 with a significance value of 0.000